IMPLEMENTASI EFISIENSI AKSES DATA SEKOLAH UNTUK GURU BERBASIS WEB STUDI KASUS PADA SEKOLAH SMP NEGERI 2 CIKANDE - Aab Abdul Basit; Heryadi; Muhammad Ikhsan Maulana (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2023)
Sekolah Menengah Pertama (SMP) Negeri 2 Cikande has problems related to the processing of value data which still uses manual recording; which will make it difficult to manage value data, the homeroom/teacher's work process will also be slow and hampered if an error occurs due to human error in the process of recording or managing large-scale data which results in the distribution of grade report cards not being submitted on time to students or parents. Another problem that arises is the absence of online media to provide information regarding teacher teaching schedules and subject schedule information. With the problems faced, the researchers have a goal to develop an academic information system to solve the problems faced. In the research that will be carried out using the extreme programming method and to test the feasibility of the system using the ISO 25010 method. With the existence of an academic information system that has been developed it can assist in processing grades more effectively and efficiently so that value data can be easily archived and easy to be made by the academic department / SMP administration staff. This academic information system also helps teachers more easily access and see grades or information about teacher schedules and subjects which are expected to make it easier for students to learn and in testing academic information systems have received a total score of 96%, with The score value is the conclusion for the system being developed has a "VERY GOOD" scale and is very feasible for the system to be implemented at SMP Negeri 2 Cikande.